Methicillin Resistant Staphylococcus aureus Prostatic Abscess with Bacteremia - Daniel J. Lachant; Michael Apostolakos; Anthony Pietropaoli (Case Reports in Infectious Diseases)
Prostatic abscess is traditionally considered a rare disease that is caused by Gram-negative bacteria. Methicillin resistant Staphylococcus aureus (MRSA) has recently emerged as an important cause of prostatic abscesses. Symptoms are nonspecific and include dysuria, urinary frequency, fever, chills, and perineal and low back pain. Morbidity and mortality increase with delays in identification and proper treatment. We present two cases of community acquired MRSA prostatic abscesses with bacteremia. One of these cases may be the first reported septic shock fatality resulting from a prostatic abscess source in an immunocompetent patient. As the number of community acquired MRSA bacteremia cases increases, this potential site of infection should be recognized.